Oligotrophic Phytoplankton Community Effectively Adjusts to Artificial Upwelling Regardless of Intensity, but Differently Among Upwelling Modes - Ortiz, Joaquin; Arístegui, Javier; Hernández-Hernández, Nauzet; Fernández-Méndez, Mar; Riebesell, Ulf (Frontiers in Marine Science, 2022)
Artificial upwelling has been proposed as a means of enhancing oceanic CO2 sequestration and/or raising fishery yields through an increase in primary production in unproductive parts of the ocean. However, evidence of its efficacy, applicability and side effects is scarce. Here we present part of the results of a 37-day mesocosm study conducted in oligotrophic waters off the coast of Gran Canaria. The goal was to assess in situ the effects of artificial upwelling on the pelagic community. Upwelling was simulated via two modes: i) a singular deep-water pulse and ii) a recurring supply every 4 days; each mode at four different intensities defined by the total amount of nitrate added: approx. 1.5, 3, 5.7, and 11 µmol L-1. In this study we focus on the phytoplankton response through size-fractionated 14C primary production rates (PP), Chlorophyll a and biomass. We observed increases in PP, accumulated PP, Chlorophyll a and biomass that scaled linearly with upwelling intensity. Upwelling primarily benefitted larger phytoplankton size fractions, causing a shift from pico- and nano- to nano- and microphytoplankton. Recurring deep-water addition produced more biomass under higher upwelling intensities than a single pulse addition. It also reached significantly higher accumulated PP per unit of added nutrients and showed a stronger reduction in percentage extracellular release with increasing upwelling intensity. These results demonstrate that oligotrophic phytoplankton communities can effectively adjust to artificial upwelling regardless of upwelling intensity, but differently depending on the upwelling mode. Recurring supply of upwelled waters generated higher efficiencies in primary production and biomass build-up than a single pulse of the same volume and nutrient load.